Randomized, double-blind, active-controlled study evaluating the safety and immunogenicity of three vaccination schedules and two dose levels of AV7909 vaccine for anthrax post-exposure prophylaxis in healthy adults. Issue 18 (19th April 2016) - Hopkins, Robert J.; Kalsi, Gurdyal; Montalvo-Lugo, Victor M.; Sharma, Mona; Wu, Yukun; Muse, Derek D.; Sheldon, Eric A.; Hampel, Frank C.; Lemiale, Laurence
Highlights: AV7909 is a combination of BioThrax ® (Anthrax Vaccine Absorbed) and CPG 7909 adjuvant. AV7909 vaccine is being developed for anthrax post-exposure prophylaxis. The safety and immunogenicity of 2 doses and 3 vaccine schedules were evaluated. Immunogenicity results indicate further study of a two dose schedule is warranted. Both doses and all vaccine schedules were well tolerated. Abstract: AV7909 vaccine being developed for post-exposure prophylaxis of anthrax disease may require fewer vaccinations and reduced amount of antigen to achieve an accelerated immune response over BioThrax ® (Anthrax Vaccine Adsorbed). A phase 2, randomized, double-blind, BioThrax vacccine-controlled study was conducted to evaluate the safety and immunogenicity of three intramuscular vaccination schedules and two dose levels of AV7909 in 168 healthy adults. Subjects were randomized at a 4:3:2:4:2 ratio to 5 groups: (1) AV7909 on Days 0/14; (2) AV7909 on Days 0/28; (3) AV7909 on Days 0/14/28; (4) half dose AV7909 on Days 0/14/28; and (5) BioThrax vaccine on Days 0/14/28. Vaccinations in all groups were well tolerated. The incidences of adverse events (AEs) were 79% for AV7909 subjects and 65% for BioThrax subjects; 92% of AV7909 subjects and 87% of BioThrax subjects having AEs reported Grade 1–2 AEs. No serious AEs were assessed as potentially vaccine-related, and no AEs of potential autoimmune etiology were reported. There was no discernible pattern indicative of a safety concern across groups in the incidence or severity of reactogenicity events. Groups 2–4 achieved success for the primary endpoint, demonstrated by a lower 95% confidence limit of the percentage of subjects with protective toxin neutralizing antibody NF50 values (≥0.56) to be ≥40% at Day 63. Group 1 marginally missed the criterion (lower bound 95% confidence limit of 39.5%). Immune responses were above this threshold for Groups 1, 3 and 4 at Day 28 and all groups at Day 42. Further study of an AV7909 two-dose schedule given 2 weeks apart is warranted in light of the favorable tolerability profile and immunogenicity response relative to three doses of BioThrax vaccine, as well as preliminary data from nonclinical studies indicating similar immune responses correlate with higher survival for AV7909 than BioThrax vaccine.